Life Cycle - San Jose State College:::::::::
Other classes, beyond the students in the originating Humanities course, were involved in events for the Survival Faire. This program, which lists the schedule of events over the week, includes an event called Life Cycle, produced by students in a Graphic Design course. (Earth Day)